ANALISIS TRANSAKSI GADAI EMAS DALAM PERSPEKTIF ISLAM (Studi Kasus Pada BMT Al Muqrin Pondok Cabe Pamulang Banten) - Imam Sofi'i (Universitas Pamulang, 2017)
ABSTRACTProducts pawn services are grounded in principles of sharia is a gold Rahn where the customer is not charged interest on loans obtained. Transactions Rahn gold, money or funds loaned bebentuk who does not expect additional aid over the debt. As the development of gold Rahn practices in Indonesia, raised doubts over the suitability of various circles of gold Rahn practices with existing concepts. The opinions stated that the practice of gold Rahn same as conventional gold pawn. The purpose of this study was to answer the gold pawn transactions in perpespektif Islam in BMT al Muqrin.Broadly speaking, that the results of this study show BMT al Muqrin already complied with the rules in the transaction Rahn gold. But there are things that are considered to be not in accordance with this concept, namely the merger agreement and contract Rahn Ijara, Ijara and administrative costs determination based on the size of the loan, as well as the lack of attention to the status of its gold holdings. Regardless of the discrepancy between the concept of the gold in the BMT Rahn practices, customer systems that do BMT al Muqrin is in conformity with Dsn-MUI Fatwa No: 25 / DSN-MUI / III / 2002 of Rahn. Excess money from the auction after deducting the costs of loans and will be returned to the customer, while if there are still shortcomings remain the obligation of the client to pay off. This is the beauty of Islam in which the redemption or repayment is done fair